Frequency of Hepatitis B Infection in Vaccinated Children with β-Thalassemia Major Receiving Multiple Transfusions - Shohab, Sara; Muntaha, Sidra Tul; Zain, Jawaria; Khan, Jawad Ahmad; Ahmad, Rafiq (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the frequency of hepatitis B infection in vaccinated children with beta thalassemia major receiving multiple blood transfusions. Methods: This was a cross-sectional study with a non-probability consecutive sampling technique conducted at the Department of Pediatrics, Cantonment General Hospital & Holy Family Hospital, Rawalpindi, from January 26, 2022, to July 26, 2022. A total of 245 children diagnosed with beta thalassemia major and receiving regular transfusion therapy were enrolled. Venous blood samples were collected and tested for hepatitis B surface antigen (HBsAg) using an enzyme-linked immunosorbent assay (ELISA). Demographic and clinical data were recorded, including age, gender, and number of transfusions. Quantitative variables, such as age and transfusion frequency, were expressed as mean ± standard deviation (SD), while qualitative variables, including gender and hepatitis B positivity, were expressed as frequencies and percentages. Results: The mean age of patients was 9.56±4.3 years. Of the total, 170 (69.4%) were male and 75 (30.6%) were female. Children receiving fewer than eight transfusions annually were 136 (55.6%), while those receiving eight or more were 109 (44.4%). Hepatitis B infection was detected in 20 children (8.2%). Conclusion: Hepatitis B infection is still prevalent in vaccinated children with transfusion-dependent beta thalassemia major and is more frequent in those receiving a higher number of blood transfusions. Strengthening blood donor screening programs and considering booster vaccination strategies may help reduce this burden. Keywords: Beta thalassemia major, Blood transfusion, Child, Hepatitis B, Vaccination